Price Hike and Nepali Students’ Perception towards Inflation - Nepal, Pramshu; Panthee, Keshav Raj (Myagdi Guru, 2024)
This study investigates the perceptions of college-level Nepali students toward inflation, a critical economic phenomenon characterized by a continuous rise in the general price level of goods and services. The research has used a quantitative approach, gathering data from 208 students of bachelor and master level in community colleges of Kathmandu and Rupandehi districts via a structured questionnaire. The survey reveals significant concern among students about inflation’s impact on their lives. The findings underscore a prevalent skepticism among students towards government-published inflation rates, reflecting broader societal doubts about economic transparency and management. The majority of respondents express concerns about how inflation impacts their personal finances, career decisions, and access to essential services like education and healthcare. Moreover, there is a notable perception among students that inflation exacerbates income inequality and poses substantial challenges to economic stability in Nepal. In the context of rising cost of living of average Nepali people, findings of such study could provide guideline for policy makers.